Hyperkinetic movement disorders - Weiner, William J.; Tolosa, Eduardo (Edinburgh : Elsevier, 2011)
Annotation A volume in the Handbook of Clinical Neurology series on hyperkinetic movement disorders. A volume in the Handbook of Clinical Neurology series, which has an unparalleled reputation as the world's most comprehensive source of information in neurology. International list of contributors including the leading workers in the field. Describes the advances which have occurred in clinical neurology and the neurosciences, their impact on the understanding of neurological disorders and on patient care.
SECTION 1 -- Choreoathetoid Diseases and Syndromes. SECTION 2 -- Immune Related Chorea. SECTION 3 -- Vascular Related Chorea. SECTION 4 -- Metabolic Disturbances. SECTION 5 -- Chorea in Other Medical Settings. SECTION 6 -- Other Syndromes. SECTION 7 -- Athetosis. SECTION 8 -- Myoclonus. SECTION 9 -- Essential Tremor. SECTION 10 -- Dystonia. SECTION 11 -- Tardive Dyskinesia. SECTION 12 -- Tics. SECTION 13 -- Other Syndromes.
Includes bibliographical references and index.
Print version record.
Keywords: Hyperkinesia; Hyperkinesis; Movement Disorders; Hyperkinesia; Electronic books